Are the Symptoms of Parkinsonism Cortical in Origin? - Gordon W. Arbuthnott; Marianela Garcia-Munoz (Computational and Structural Biotechnology Journal, 2017)
We present three reasons to suspect that the major deleterious consequence of dopamine loss from the striatum is a cortical malfunction. We suggest that it is cortex, rather than striatum, that should be considered as the source of the debilitating symptoms of Parkinson's disease (PD) since: 1. Cortical synapses onto striatal dendritic spines are lost in PD. 2. All known treatments of the symptoms of PD disrupt beta oscillations. Oscillations that are also disrupted following antidromic activation of cortical neurons. 3. The final output of basal ganglia directly modulates thalamic connections to layer I of frontal cortical areas, regions intimately associated with motor behaviour.These three reasons combined with evidence that the current summary diagram of the basal ganglia involvement in PD is imprecise at best, suggest that a re-orientation of the treatment strategies towards cortical, rather than striatal malfunction, is overdue. Keywords: Parkinson's disease, Deep brain stimulation, Layer I, Motor cortex